The Skilled Approach in Arabic Learning at Islam Burapha Witya School Narathiwat, Thailand - Rihanatul Fauziah; Yuli Imawan (Arabic Education Program IAIN Pekalongan, 2020)
In this study, the author will describe learning Arabic with a skills approach at the Burapha Witya Narathiwat Islamic school in Thailand which aims to provide innovation in a fun and skilled Arabic learning that can master four aspects of language skills including listening, speaking, reading and writing as well as motivating students to be able to learn Arabic easily so that they can practice it in their daily life. This research uses qualitative research methods, namely descriptive analysis with a case study approach, data collection techniques in the form of observation, interviews and documentation. The results of the study state that learning Arabic with a skills approach can provide innovation and motivation in learning Arabic for students and Arabic teachers because students can play an active role directly in various kinds of learning language skills according to the level of ability possessed by each student. in their field so that students can learn Arabic with ease and fun and can master four aspects of language skills including listening, speaking, reading and writing. Thus students can practice Arabic in everyday life.